2015
DOI: 10.1159/000369828
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Soluble Thrombomodulin Treatment for Acute Exacerbation of Idiopathic Pulmonary Fibrosis: A Retrospective Study

Abstract: Background: Acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF) can be fatal, and abnormalities in the coagulation system of patients with AE-IPF have been reported. Recombinant human soluble thrombomodulin (rhTM) forms a complex with thrombin to inactivate coagulation. It also inhibits high-mobility group box protein 1 (HMGB-1), which results in the suppression of inflammation. Objectives: We aimed to evaluate the effectiveness of rhTM for the treatment of AE-IPF. Methods: We retrospectively reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 27 publications
3
60
1
Order By: Relevance
“…A total of 11 citations were identified, and after screening, five publications were included in the review [9][10][11][12][13]. All studies were reported from Japan.…”
Section: Search and Selection Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 11 citations were identified, and after screening, five publications were included in the review [9][10][11][12][13]. All studies were reported from Japan.…”
Section: Search and Selection Resultsmentioning
confidence: 99%
“…Of enrolled five studies, three were prospective, historical control studies [9,10,13] and two were retrospective studies (11,12). The five studies recruited a total of 77 patients receiving rhTM treatment (rhTM group).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an analysis of acute exacerbation of idiopathic pulmonary fibrosis, Isshiki et al compared outcomes in patients treated with rTM and conventional therapy [10]. That study found that patients treated with rTM had better survival over 90 days.…”
Section: Discussionmentioning
confidence: 99%